Assessing experts' perspectives on challenges in substance misuse prevention, harm reduction, and treatment to shape funding priorities in New York State - Daniel J. Kruger; Hilary M. Kirk; Kenneth E. Leonard; Joshua J. Lynch; Nancy Nielsen; R. Lorraine Collins; Joseph W. Ditre; Debbian Fletcher-Blake; Susan A. Green; Aaron Hogue; Julia K. Hunter; John M. Marraffa; et al. (BMC, 2024)
Abstract Background Drug overdose is a leading cause of death and opioid-related deaths increased by more than 300% from 2010 to 2020 in New York State. Experts holding a range of senior leadership positions from across New York State were asked to identify the greatest challenges in substance misuse prevention, harm reduction, and treatment continuum of care. Expert input was used to shape funding priorities. Method Individual semi-structured interviews of sixteen experts were conducted in April and May 2023. Experts included academics, medical directors, leaders of substance misuse service agencies, administrators of a state agency, a county mental health commissioner, the president of a pharmacy chain, and a senior vice president of an addiction-related national non-profit. Zoom interviews were conducted individually by an experienced qualitative interviewer and were recorded, transcribed, and coded for content. An initial report, with the results of the interviews organized by thematic content, was reviewed by the research team and emailed to the expert interviewees for feedback. Results The research team identified five major themes: 1. Siloed and fragmented care delivery systems; 2. Need for a skilled workforce; 3. Attitudes towards addiction (stigma); 4. Limitations in treatment access; and 5. Social and drug related environmental factors. Most experts identified challenges in each major theme; over three-quarters identified issues related to siloed and fragmented systems and the need for a skilled workforce. Each expert mentioned more than one theme, three experts mentioned all five themes and six experts mentioned four themes. Conclusions Research, educational, and programmatic agendas should focus on identified topics as a means of improving the lives of patients at risk for or suffering from substance use-related disorders. The results of this project informed funding of pilot interventions designed to address the identified care challenges.